259 AN AUDIT OF DNACPR FORM USAGE IN A LEVEL 4 HOSPITAL FOLLOWING RE-DESIGN AND IMPLICATIONS FOR ITS FUTURE USE. (25th October 2022) - Brennan, F; Higgins, M; Russell, S; Sands, H; Keogh, C; Curran, C
Abstract: Background: In 2020 during the Covid-19 pandemic our hospital introduced a new green DNACPR form with 2 significant changes. It now specifies if the patient is or is not for resuscitation (as a yes/no choice) and a Treatment Escalation Plan (TEP) has moved to the front of the page from the back. A subsequent audit found that 19% of inpatients had forms completed, of which 68% stated DNACPR and 29% for CPR. 76% of forms had a TEP (versus 56% on the old forms). We repeated the hospital wide audit in 2022 to assess if the improvement in TEP documentation was sustained, and if it was used on all patients or primarily to document DNACPR decisions. Methods: The hospital-wide audit was performed on the 25.05.2022. Charts were reviewed on medical and surgical wards. ICU patients were excluded. The following data were recorded: Resuscitation status, form completion, presence of a TEP, if the date of admission and form completion were recorded, if the name of doctor and nature of discussion with patient and family were documented, and if the TEP was consistent with the most recent clinical notes. The data was compared to the 2020 audit and against the Hospital's DNAR & TEP policy. Results: 634 inpatients were identified. 15.7% (100) had a form completed of which 92% stated DNAR. One of these did not have a TEP. The doctor's name and grade were clearly documented on all forms. Conclusion: 99% of patients who were not for CPR had a TEP indicating sustained improvement since the introduction of the new form. Given 83.3% of patients did not have any documented resuscitation status the approach of documenting yes or no for resuscitation is not being utilised. A return to a dedicated form that indicates someone should not undergo attempts at resuscitation may offer more clarity.